2019
DOI: 10.21203/rs.2.13294/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addressing socio-cultural barriers to family planning and co-designing services to improve utilization: evidence from northern Nigeria

Abstract: BACKGROUND: Family planning is a proven cost-effective intervention that has contributed to women empowerment and overall human development. Demand factors and women’s expectations and experiences at health facility for family planning services may influence their uptake and utilisation of these services. Increased awareness and positive community perception and quality of family planning services that meet clients’ expectations may greatly improve utilization. The aim of this study was to identify ways to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, a study from Nigeria also reported that the majority of the women can identify obstetric danger signs. 12 On the contrary, studies carried out in Northern 13 and another study from Ethiopia 14 reported a low level of identification of obstetric danger signs.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, a study from Nigeria also reported that the majority of the women can identify obstetric danger signs. 12 On the contrary, studies carried out in Northern 13 and another study from Ethiopia 14 reported a low level of identification of obstetric danger signs.…”
Section: Discussionmentioning
confidence: 95%
“…After screening the title and abstract of 6183 papers (excluding duplicates) for relevance to the subject, 131 papers were selected. A total of 67 articles [ 1 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Methodsmentioning
confidence: 99%